Parametrically amplified Josephson plasma waves in YBa 2 Cu 3 O 6+ x : Evidence for local superconducting fluctuations up to the pseudogap temperature T ∗ - Marios H. Michael; Eugene Demler; Patrick A. Lee (Proceedings of the National Academy of Sciences, 2026)
Experiments that subject underdoped YBa 2 Cu 3 O 6+ x (YBCO) to intense terahertz pulses at temperatures between the transition temperature T c and the pseudogap scale T ∗ have revealed a reflectivity edge that resembles that of the superconducting state, together with second harmonic generation of a probe pulse modulated at a similar frequency. These have been interpreted in terms of parametric amplification of the lower Josephson plasmon mode. Since this mode is often associated with coherent oscillations between bilayers in the YBCO structure, these experiments have led to the suggestion that the intense pump has created (or revealed) in-plane pair coherence up to T ∗ ≈ 400 K. In this paper we propose an alternative explanation by assuming the existence of local pair amplitude and phase at equilibrium for T c < T < T ∗ . The phase correlation spans only a few lattice constants and we do not assume any pump-induced enhancement of this correlation, either in-plane or between bilayers. Instead, the coherent drive, via a parametric amplification process, induces coherence in the Josephson currents between members of bilayers. When combined with a Floquet framework, the reflectivity data can be explained. The key point is that in the lower Josephson plasmon, the coupling between bilayers is mainly capacitive; the Josephson current between bilayers can be set to zero without strongly affecting the parametric amplification process. Importantly, while superconducting coherence may not be created by the pump, the pseudogap phase must possess a local pairing amplitude at equilibrium. Consequently, these experiments have strong implications for the understanding of the pseudogap phase.